Analisis perubahan dalam bentuk bantuan pemerintah terhadap kemiskinan di kota Medan - Juliana Nasution; Rahmat Hidayat; Samsi Efendi; Fajar Nugraha; Asrul Aswinata (Universitas Muhammadiyah Enrekang, 2022)
The purposeof this researchwas to determine themodel ofpoverty alleviationin Medan City through econometric approach. This research usedsecondary datatime trend(time series) of the years 2000-2010. The methodof analysis usedis the econometric method with variables that affect povertyis economic growth, income per capita, inflation and unemploymen tareprocessed usin the program eviews 5.1.The modelis thedata analysis using multiple linear regression Ordinary Least Square method (OLS). The results showed that the number of poor people in the city of Medan relatively large approximately 10,05% of the population of the city of Medan in 2010. Test results showed variable estimates of economic growth and per capita income has negative and statistically significant, while inflation and unemployment variables have a positive and significant impact on the number of poor people in the city of Medan.